Developing a user-based decision-aid framework for water storage systems in Sub-Saharan Africa: the sase of Blue Nile Basin in Ethiopia - Xenarios, Stefanos; Polatidis, H.; McCartney, Matthew P.; Nemes, A. (World Scientific Publishing, 2015)
The development of water storage schemes in Sub-Saharan Africa (SSA) is considered a major aid for those regions with unequal water distribution, limited accessibility and anticipated climate change impacts. Great attention is given by many SSA countries to set up different water storage schemes that may improve rural and urban development on a national level. The funding for the water storage schemes is often derived from foreign agencies which conduct feasibility studies for the financing of potential investments. Often however, the feasibility studies rely on a single monetary criterion which may not identify the most appropriate water storage in each case. In addition, limited data availability in many SSA countries increases the difficulty of identifying the most suitable storage option. This paper develops a multicriteria framework for the integrated evaluation of water storage strategies in Sub-Saharan African countries. A set of economic, agronomic and opinion-based criteria are assessed through the PROMETHEE II outranking approach. The introduction of crop modeling complements the limited field data available in agronomic criteria and enhances the scientific rigor of the method. Ethiopia is adopted as a representative case of SSA countries where a diverse set of water storage options is currently under construction, often financed by foreign agencies.